Study on Mechanical Properties and Delamination Factor Evaluation of Chemically Treated Nettle Fiber Reinforced Polymer Composites - Pankaj; Chandrashekhar Jawalkar; Suman Kant (Journal of Natural Fibers, 2023)
The exceptional benefits of natural fibers like high weight ratio, biodegradable and low density increased the usage of natural fibers reinforcement in polymers that has increased in recent years. To enhance bonding strength between polymers and natural fibers, this research paper is focused on the possibility of utilizing epoxy resin and nettle fiber to develop a biocomposite. In addition to that surface modification of nettle fibers has been done using different concentration of NaOH, KOH, and NaHCO3. The treated fibers were then reinforced in the epoxy resin to investigate the influence of chemicals on the mechanical properties of developed composites by performing tensile strength, flexural strength, and impact strength. The investigation results revealed that during the experimental investigation, maximum tensile strength (30.13 MPa), flexural strength (22.36 MPa), and impact strength (9.21 J) were discovered for 5% NaOH. Besides the mechanical testing, the fabricated composites were conventionally drilled to investigate the effect of spindle speed (50–800 rev/min), feed rate (0.125–1.2 mm/min), and drill diameter (4–8 mm). The study suggested increase in delamination factor at a higher feed rate and drill diameter. SEM was done on the drilled hole to observe the delamination damage.